Outcomes of dementia: systematic review and meta-analysis of hospital administrative database studies - Rao,A; Suliman,A; Vuik,S; Aylin,P; Darzi,A (Archives of Gerontology and Geriatrics, 2016)
INTRODUCTION: Aim of the study was to compare various outcomes of dementia patients with elderly patients without dementia by conducting a systematic review of previous population-based studies. METHODS: The relevant studies were retrieved from search of electronic databases. RESULTS: The pooled data from included 11 studies consisted of outcomes of 1,044,131 dementia patients compared to 9,639,027 elderly patients without dementia. Meta-analysis showed that the mortality in dementia patients was 15.3% as compared to 8.7% in non-dementia cases (RR 1.70, CI 95%, 1.27-2.28, p 0.0004). However, there was significant heterogeneity between the studies (p<0.00001). Dementia patients had significantly increased overall readmission rate (OR 1.18; 95% CI, 1.08-1.29, p<0.001). They had higher complication rates for urinary tract infections (RR 2.88; 95% CI, 2.45-3.40, p<0.0001), pressure ulcers (RR 184; 95% CI, 1.31-1.46, p<0.0001), pneumonia (RR 1.66; 95% CI, 1.36-2.02, p<0.0001), delirium (RR 3.10; 95% CI, 2.31-4.15, p<0.0001), and, dehydration and electrolyte imbalance (RR 1.87; 95% CI, 1.55-2.25, p<0.0001). Dementia patients had more acute cardiac events (HR 1.16; 95% CI, 1.06-1.28, p 0.002), while fewer revascularization procedures (HR 0.12; 95% CI, 0.08-0.20, p<0.001). Patients with dementia had lesser use of ITU (reduction by 7.5%; 95% CI, 6.9-8.1), ventilation (reduction by 5.4%; 95% CI, 5.0-5.9), and dialysis (reduction by 0.5%; 95% CI, 0.4-0.8). DISCUSSION: Compared to older adult population, patients with dementia had poorer outcome. Despite higher mortality rate and readmission rate, they underwent fewer interventions and procedures.